2018
DOI: 10.7150/jca.23716
|View full text |Cite
|
Sign up to set email alerts
|

From First Line to Sequential Treatment in the Management of Metastatic Pancreatic Cancer

Abstract: The current management of patients with metastatic pancreatic ductal adenocarcinoma (mPDAC) is based on systemic chemotherapy. The results of the MPACT and PRODIGE clinical trials have demonstrated that the combination of nab-paclitaxel and gemcitabine (GEM) as well as FOLFIRINOX regimen result in improvement in overall survival when compared to GEM alone. Treatment guidelines now recommend either one of these two regimens as first line treatment for fit patients with mPDAC. Because no head-to-head comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 67 publications
(105 reference statements)
0
36
0
Order By: Relevance
“…Retrospective studies showed extended overall survival with a second line in patients previously treated with gemcitabine-based therapies with a median overall survival of 12 to 15 months. 6 But the good response to second line was apparently influenced by longer first-line progression-free survival in these reports. 9 …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Retrospective studies showed extended overall survival with a second line in patients previously treated with gemcitabine-based therapies with a median overall survival of 12 to 15 months. 6 But the good response to second line was apparently influenced by longer first-line progression-free survival in these reports. 9 …”
Section: Discussionmentioning
confidence: 78%
“…Treatment decisions and prognostic differ according to patient- and disease-related factors. Variables associated with better outcomes are: <65 years old, 3 excellent performance status, tumors in the head of the pancreas, 6 low level of serum Ca19.9. 8 Surgery to the primary tumor and surgery of the metastatic disease are also associated with better overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multiagent adjuvant therapy (modified folforinox) has been demonstrated to be more effective than gemcitabine alone in the adjuvant setting, but its use is limited only to patients with excellent performance status (5). Recently it has suggested that gemcitabine plus capecitabine is a valid option for these patients since it has been shown that it is more efficient than gemcitabine alone (6).…”
Section: Introductionmentioning
confidence: 99%
“…Gemcitabine is the first-line drug for chemotherapy in pancreatic carcinoma. Although the application of gemcitabine has a certain effect in terms of clinical benefit, it has limited control of progression of pancreatic carcinoma[5,6]. However, chemoresistance is a tough barrier in the treatment of pancreatic carcinoma, and the prognostic study has confirmed that the clinical effectiveness of gemcitabine is below 20%[7,8].…”
Section: Introductionmentioning
confidence: 99%